Teacher Morale and Mental Health at the Conclusion of the COVID-19 Pandemic - Tim Pressley; David T. Marshall; Savanna M. Love; Natalie M. Neugebauer (MDPI AG, 2023)
As teachers entered the 2021-2022 school year, schools tasked teachers with the challenge of closing the learning loss gap, maintaining the same standards as a typical school year, implementing COVID-19 safety protocols and teaching to grade-level standards. The current study used the theoretical framework of teacher demoralization to explore teachers' experiences of morale and mental health at the end of the 2021-2022 school year. The participants included 830 PK-12 individual teachers from across the United States who completed an online survey. The data were analysed using Pearson's correlation and the hierarchical multiple regression model to determine the predictor variables. The results showed significant predictors for both teacher morale and mental health. The implications focus on steps that school leaders can take to support teachers' morale and mental health.